Fertility as a Priority among At-Risk Adolescent Males Newly Diagnosed with Cancer and Their Parents - Klosky, James L. (Support Care Cancer, 2014)
PURPOSE: Infertility is a frequent consequence of cancer therapy and is often associated with psychological distress. Although adult survivors prioritize fertility and parenthood, this issue remains unexplored among adolescent males. This study examined future fertility as a priority (relative to other life goals) at time of diagnosis for at-risk adolescents and their parents. METHODS: Newly diagnosed adolescent males (n=96; age=13.0-21.9 years) at increased risk for infertility secondary to cancer treatment prioritized eight life goals: to have school/work success, children, friends, wealth, health, a nice home, faith, and a romantic relationship. Patients' parents (fathers, n=30; mothers, n=61) rank-ordered the same priorities for their children. RESULTS: “Having children” was ranked as a “top 3” life goal among 43.8% of adolescents, 36.7% of fathers, and 21.3% of mothers. Fertility ranked 3(rd) among adolescents, 4(th) among fathers, and 5(th) among mothers. Future health was ranked the top priority across groups, distinct from all other goals (ps<.001), and fertility ranked higher than home ownership and wealth for all groups (ps<.001). For adolescents, low/moderate fertility risk perception was associated with higher fertility rankings than no/high risk perceptions (p=.01). CONCLUSIONS: Good health is the most important life goal among adolescents newly diagnosed with cancer and their parents. In this relatively small sample, adolescents prioritized fertility as a top goal, parents also rated fertility as being more important than home ownership and financial wealth. Health care providers should communicate fertility risk and preservation options at diagnosis and facilitate timely discussion among families, who may differ in prioritization of future fertility.